2016
DOI: 10.1080/01658107.2016.1198917
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Optic Disc Drusen after Papilloedema from Idiopathic Intracranial Hypertension: On the Possible Formation of Optic Disc Drusen

Abstract: This is a 25-year observational retrospective review of 372 consecutive participants with optic disc drusen or resolved papilloedema from idiopathic intracranial hypertension. The prevalence of optic disc drusen at 19% among eyes with resolved papilloedema was approximately 10 times higher and significantly increased (p < 0.001) as compared with the occurrence in the general population. Eyes with both resolved papilloedema and optic disc drusen had similar visual acuity and visual field outcome as compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
2
16
0
1
Order By: Relevance
“…To date, there is no substantial evidence that the hyperreflective mass-like structures, almost always located in the peripapillary circumference, and described and visualized in several papers, in fact represent ODD. A study by Birnbaum et al (2016) found an extraordinarily high ODD prevalence (19%) in patients with idiopathic intracranial hypertension. A study by Birnbaum et al (2016) found an extraordinarily high ODD prevalence (19%) in patients with idiopathic intracranial hypertension.…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 98%
See 2 more Smart Citations
“…To date, there is no substantial evidence that the hyperreflective mass-like structures, almost always located in the peripapillary circumference, and described and visualized in several papers, in fact represent ODD. A study by Birnbaum et al (2016) found an extraordinarily high ODD prevalence (19%) in patients with idiopathic intracranial hypertension. A study by Birnbaum et al (2016) found an extraordinarily high ODD prevalence (19%) in patients with idiopathic intracranial hypertension.…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 98%
“…It is more likely that these structures represent disruption of retinal layers caused by local axoplasmic build-up, as they are also found in patients with idiopathic intracranial hypertension (Malmqvist et al 2017a) and optic nerve tumours (Lee et al 2015). A study by Birnbaum et al (2016) found an extraordinarily high ODD prevalence (19%) in patients with idiopathic intracranial hypertension. The high number of ODD patients in the group is most likely a result of misdiagnosing hyperreflective masslike structures as ODD and not as a disruption of retinal layers.…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 99%
See 1 more Smart Citation
“…PTS'li hastalarda ODD prevalansının normal popülasyondan daha yüksek oranda görüldüğü, hatta uzun süren papil ödem sonrası ODD oluştuğu düşünülmektedir. 15 Bu birliktelik çalışmamızda %7,4 idi. Bu bulgular ışığında, ODD tanısı alan hastalarda gerçek papil ödem birlikteliği de düşünülmeli, periyodik takip ve tetkik yapılmalıdır.…”
Section: Discussionunclassified
“…116 Reviewing 372 patients with ONHD or resolved papilloedema from IIH, others found 19% of resolved papilloedema eyes to have ONHD but this was also based on outdated OCT definitions and uncertain diagnostic criteria. 117 Acquired ONHD is not widely recognised as a common outcome after papilloedema. It may simply be that neurological patients with headaches have their optic discs examined closely, and that ONHD may be detected more often in this broad group.…”
Section: Papilloedemamentioning
confidence: 99%